Port Readiness in Facing Globalization: Indonesian Case Study - Ariadno, Melda Kamil; Afriansyah, Arie; Dewi, Yetty Komalasari (UI Scholars Hub, 2014)
International trade cannot be separated from the role of international shipping. More than 80% of goods transported through sea from a region to another, from one Country to another Country. Since the dawn of the voyage, port cannot be separated from the voyage itself. Adequate port will ensure a good international shipping. Increasing number of international shipping also means increasing volume of international trade. With a variety of factors such as geographical factor, natural resources, and population, Indonesia should be a key player in international trade by sea. However, the reality is still far from ideal, especially when compared with neighboring countries. This research aims to map the condition and situation of ports in Indonesia, especially in the legal field so that can be known what things that can be recommended to optimize the role of Indonesian ports in international trade by sea.